Training in participatory program development the case of researcher broadcasters in Radyo DZLB in Los Banos, Laguna, Philippines - Marcos-Balinos, Aiza (The Philippine Journal of Development Communication, 2013)
The study determined how a training-workshop on participatory program development conducted by Radyo DZLB of the College of Development Communication (CDC) in the University of the Philippines Los Banos (UPLB) was perceived by its participants to have affected their performance as researcher-broadcasters.